Design and Syntheses of Highly Potent Teixobactin Analogues against Staphylococcus aureus, Methicillin-Resistant Staphylococcus aureus (MRSA), and Vancomycin-Resistant Enterococci (VRE) in Vitro and in Vivo - Parmar, Anish (2018)
The cyclic depsipeptide, teixobactin, kills a number of Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), and Mycobacterium tuberculosis without detectable resistance. To date, teixobactin is the only molecule in its class that has shown in vivo antibacterial efficacy. In this work, we designed and synthesized 10 new in vivo ready teixobactin analogues. These analogues showed highly potent antibacterial activities against Staphylococcus aureus, MRSA, and vancomycin-resistant enterococci (VRE) in vitro. One analogue, d-Arg4-Leu10-teixobactin, 2, was found to be noncytotoxic in vitro and in vivo. Moreover, topical instillation of peptide 2 in a mouse model of S. aureus keratitis decreased the bacterial bioburden (>99.0% reduction) and corneal edema significantly as compared to untreated mouse corneas. Collectively, our results have established the high therapeutic potential of a teixobactin analogue in attenuating bacterial infections and associated severities in vivo.